The bidirectional enigma of glaucoma and anxiety: from neuroinflammatory mechanisms to mind-body integrated therapies - Lin, Bin; Tang, Jing; Liang, Wei; Li, Dong-kan (Frontiers in Psychiatry, 2025)
IntroductionGlaucoma, a leading cause of irreversible global blindness, has a bidirectional association with anxiety that worsens both conditions. Anxiety prevalence in glaucoma patients (19.07%–25.71%) is much higher than the general population’s 9.8%, and glaucoma patients have a 4.45-fold higher anxiety risk than healthy controls, underscoring the need to synthesize their interactions and interventions.MethodsA systematic search of PubMed, Web of Science, and Embase (2010–2025) identified studies on glaucoma-anxiety bidirectional relationships, mechanisms, and interventions. Following PRISMA guidelines, 99 studies were screened, with 14 eligible for synthesis.ResultsBidirectional pathogenesis involves three pathways: (1) Anxiety accelerates glaucoma via hypothalamic-pituitary-adrenal axis overactivation (43% lower retinal ganglion cell [RGC] survival), sympathetic catecholamine release, and microglial IL-1β/TNF-α secretion (P<0.001); (2) Glaucoma induces anxiety through RGC apoptosis-driven HMGB1/TLR4/NF-κB activation and abnormal amygdalar connectivity; (3) Anxiety correlates with 40% reduced treatment adherence, faster visual field progression (-1.5 dB/year), and 30% higher postoperative complications. Gaps include limited longitudinal data and unstandardized psychological interventions.Discussion“Mind-body integrated therapy” is prioritized: cognitive-behavioral therapy boosts adherence by 76%, biofeedback lowers intraocular pressure by 4.8 mmHg, and SSRIs alleviate anxiety safely. Future research should focus on biomarker-guided and anti-inflammatory interventions to shift management toward physiological-psychological co-care.